2001
DOI: 10.1080/02626660109492801
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological implications of the Southern Oscillation: variability of the rainfall-runoff relationship

Abstract: A connection between El Nino Southern Oscillation (ENSO) and weather phenomena in eastern Australia has been recognized for several decades. However, little work has been devoted to addressing how this correlation affects hydrological system behaviour within regional-scale catchments. In this study, spatially distributed ENSO effects are evaluated in terms of monthly rainfall, evaporation, streamflow and runoff characteristics for a 1300 km 2 catchment. The catchment is located in southeastern Australia where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…This finding in the Border Rivers Catchment is in congruence with that of Wooldridge et al (2001) (study conducted in eastern Australia) and Zubair (2003) (study conducted in Mahaweli River Basin in Sri Lanka) who found that the ENSO relationship with streamflow is stronger than that of rainfall.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This finding in the Border Rivers Catchment is in congruence with that of Wooldridge et al (2001) (study conducted in eastern Australia) and Zubair (2003) (study conducted in Mahaweli River Basin in Sri Lanka) who found that the ENSO relationship with streamflow is stronger than that of rainfall.…”
Section: Discussionsupporting
confidence: 77%
“…Rainfall-runoff responses are typically nonlinear (Wooldridge et al, 2001, Zubair, 2003. In practice, runoff in these environments is threshold driven.…”
Section: Resultsmentioning
confidence: 99%
“…Orographic enhancement results in the highest rainfall totals occurring in the northern part of the catchment where the average annual rainfall is approximately 1600 mm. The lowest annual rainfall occurs over the central part of the catchment while further south coastal influences reverse the rainfall gradient and annual rainfall increases to approximately 1100 mm at Raymond Terrace (Wooldridge et al, 2001). Figure 2 shows the average monthly rainfall totals and their variance for the Williams River catchment .…”
Section: Study Catchment-the Williams River New South Walesmentioning
confidence: 99%
“…However, the rainfall-runoff regression relationships used by Cai and Cowan (2008b) do not take into account any soil moisture carryover and therefore the inherent nonlinearity in the rainfall-runoff relationship (e.g. Wooldridge et al, 2001), and the importance of antecedent soil moisture conditions (e.g. Kiem and Verdon-Kidd, 2009), is likely to have been underestimated (e.g.…”
Section: Hydrological Implications Of the Post-1994 Change In Rainfalmentioning
confidence: 99%